Logical Turn and Practical Path of Teacher Exchange and Rotation System: Based on Professional Capital - ZHANG Wenli (Jiaoshi jiaoyu xuebao)
Teachers exchange and rotation system is an important measure to optimize teacher allocation, narrow the urban-rural education gap, and promote the high-quality and balanced development of compulsory education. The current teacher exchange and rotation system follows the logical path of resource allocation, and faces challenges such as the inversion of goals and means under the orientation of "compensation", and the concealment of individual rationality of teachers under the instrumentalization of human resources. Since the compulsory education has entered a new stage of development, the value proposition of the teacher exchange and rotation system should transition from "changing position" to "providing shared high-quality education". It is argued that the original basis of the system of no longer meets the new needs of compulsory education. Exchange and rotation is essentially the cross-domain flow and proliferation of teachers' professional capital. And professional capital theory can provide new ideas for interpreting the teachers exchange and rotation system. Essence Based on the perspective of professional capital, taking the professional development of rotating teachers as an intermediate variable of the high-quality balance of the exchange and rotation system and the compulsory education system, this paper explores the logical turn of the system from the perspectives of value orientation, teacher positioning, equilibrium mode, and driving mechanism. On this basis, a knowledge creation support system should be established through the spread of human capital; it is to build a community of professional development through the accumulation of social capital; generate decision-making capital to ensure the professional autonomy of rotating teachers, and to further improve the implementation of the system.